find the values of a, b and c in the equation below (x^5yz^4)^3/x^3yz= x^a y^b z^c
![find the values of a b and c in the equation below x5yz43x3yz xa yb zc class=](https://us-static.z-dn.net/files/d70/10f7512abc9d309d885a0ce959e4b72a.jpg)
Answer: a = 12, b = 2, c = 11
Step-by-step explanation:
Using exponent rules we can distribute the exponent of 3 to the xyz.
This results in the numerator now being. [tex]x^{5*3}+y^{1*3}+z^{4*3}\\[/tex] This can be simplified to, [tex]x^{15}y^{3}z^{12}\\[/tex].
Now divide the numerator by the denominator subtracting the exponents.
Which equals, [tex]x^{12}y^{2}z^{11}[/tex]
So a = 12
b = 2
and
c = 11
The values of [tex]a, \ b,\ c[/tex] are [tex]12,\ 2,\ 11[/tex] .
Exponent indicates that the base is to be raised to a certain power. So, it is the power of the base.
We have,
[tex]\frac{(x^5yz^4)^3}{x^3yz}=x^ay^bz^c[/tex]
Now simplify the above given equation;
[tex]\frac{(x^5*3y^1*3z^4*3)}{x^3yz}=x^ay^bz^c[/tex]
[tex]\frac{(x^{15}y^3z^{12})}{x^3yz}=x^ay^bz^c[/tex]
Now, Using the exponent rule;
[tex]\frac{a^n}{a^m} = a^{n-m}[/tex]
So,
[tex](x^{15-3}y^{3-1}z^{12-1})=x^ay^bz^c[/tex]
[tex](x^{12}y^{2}z^{11})=x^ay^bz^c[/tex]
Now,
As we see variables on both sides of equation are same (i.e. bases of powers are same), so now compare the powers of sides of variables;
⇒ [tex]x^{12}=x^a[/tex]
[tex]a=12[/tex],
And, [tex]y^2=y^b[/tex]
[tex]b=2[/tex]
And, [tex]z^{11}=z^c[/tex]
[tex]c=11[/tex]
So, the values of [tex]a, \ b,\ c[/tex] are [tex]12,\ 2,\ 11[/tex] which are find out using the exponent rule.
Hence, we can say that the values of [tex]a, \ b,\ c[/tex] are [tex]12,\ 2,\ 11[/tex] .
To know more about exponent click here
https://brainly.com/question/5497425
#SPJ3